Predictors of employment among cancer survivors after medical rehabilitation - a prospective study - Anja Mehnert; Uwe Koch (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: This study aimed to (i) investigate cancer survivor's employment status one year after the completion of a medical rehabilitation program and (ii) identify demographic, cancer, and psychosocial, treatment-, and work-related predictors of return to work (RTW) and time until RTW. METHODS: A total of 1520 eligible patients were consecutively recruited on average 11 months post diagnosis and assessed at the beginning (t_0) (N=1148) and end of rehabilitation (t_1) (N=1060) and 12 months after rehabilitation (t_2) (N=750). Participants completed validated measures assessing functional impairments, pain, anxiety, depression, quality of life, social support, and work-related characteristics including work ability, sick leave absence, job requirements, work satisfaction, self-perceived employer accommodation, and perceived job loss. Physicians estimated the degree of cancer-entity-specific functional impairment. RESULTS: In a mean time of six weeks after rehabilitation, 568 patients (76%) had returned to work. The multivariate hierarchical logistic regression analysis indicated that baseline RTW intention [odds ratio (OR) 6.22, 95% confidence interval (95% CI) 1.98-19.51], perceived employer accommodation (OR 1.93, 95% CI 0.33-0.99), high job requirements (OR=1.84, 95% CI 1.02-3.30), cancer recurrence or progression (OR=0.27, 95% CI 0.12 - 0.63), baseline sick leave absence (OR=0.26, 95% CI 0.09-0.77), and problematic social interactions (OR=0.58, 95% CI 0.33-0.99) emerged as significant predictors for RTW. The explained variance of the total model was Nagelkerke's R^²=0.59 (P<0.001). CONCLUSION: Our findings emphasize the high relevance of motivational factors. Occupational motivation and skepticism towards returning to work should be carefully assessed at the planning of the rehabilitation program.